2019
DOI: 10.1021/acsami.9b01433
|View full text |Cite
|
Sign up to set email alerts
|

Tailored Design of an ROS-Responsive Drug Release Platform for Enhanced Tumor Therapy via “Sequential Induced Activation Processes”

Abstract: The reactive oxygen species (ROS)-responsive intelligent drug delivery system has developed rapidly in recent years. However, because of the low concentration of ROS in most types of tumor cells, it is not possible to rapidly and effectively stimulate the drug delivery system to release the active drug. Here, we introduced “sequential induced activation processes” for efficient tumor therapy by designing a new ROS-responsive drug release platform. β-Lapachone, a positively charged nitrogen mustard (NM) prodrug… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0
1

Year Published

2020
2020
2025
2025

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(17 citation statements)
references
References 35 publications
0
16
0
1
Order By: Relevance
“…3.1. PPT prodrug designed and self-assembly (Lv et al, 2014;Luan et al, 2019;Xu et al, 2020). The polyamine acid chain can be decomposed by enzymatic hydrolysis of the peptide bond, and the degradation product can be applied to the life cycle of the organism (Guo et al, 2020).…”
Section: Resultsmentioning
confidence: 99%
“…3.1. PPT prodrug designed and self-assembly (Lv et al, 2014;Luan et al, 2019;Xu et al, 2020). The polyamine acid chain can be decomposed by enzymatic hydrolysis of the peptide bond, and the degradation product can be applied to the life cycle of the organism (Guo et al, 2020).…”
Section: Resultsmentioning
confidence: 99%
“…Some studies reported that the ROS in tumors was insufficent to rapidly and effectively stimulate the drug delivery. To address this issue, Luan et al introduced "sequential induced activation process" to the ROS-responsive nanoplatform [83], where β-lapachone (a ROSsensitive nitrogen mustard prodrug) and two diblock polymers were self-assembled to form nanoparticles favorable for drug delivery. At tumor sites, the release of β-lapachone induced the generation of H 2 O 2 , which triggered the ROS-sensitive nitrogen mustard prodrug to form the active nitrogen mustard, leading to the cellular apoptosis.…”
Section: Hypoxiamentioning
confidence: 99%
“…In contrast, polyamino acid chains are characterized by remarkable biocompatibility, perfect biodegradability, and low toxicity [144,145]. Therefore, Luan et al formed nanoparticle(P-NM-Lapa) with polyaspartic acid-acetylated maltoheptaose (PAsp-AcMH) composed of (AcMH) and (PAsp), mPEG-AcMH composed of AcMH and nontoxic PEG, and β-lapachone and positively charged nitrogen mustard (NM) prodrug [36]. P-NM-Lapa decomposes AcMH in an acidic environment, releasing β-lapachone and NM prodrugs.…”
Section: Sequential Drug Release Where One Of the Co-loaded Drugs Ampmentioning
confidence: 99%
“…Therefore, this means that P-NM-Lapa is more stable in the body and has no toxic side effects compared to when DOX was administered. In addition, by using β-lapachone together with a NM prodrug that reacts with H 2 O 2 and has less toxicity, a synergistic effect and selective expression in cancer cells can be realized [36].…”
Section: Sequential Drug Release Where One Of the Co-loaded Drugs Ampmentioning
confidence: 99%